ORGANIZATIONAL DEVELOPMENT TO INCREASE AN ORGANIZATIONS EFFECTIVENESS AND COMPETITIVENESS TO IMPROVE EMPLOYEE SATISFACTION, PRODUCTIVITY IN ORDER TO STRENGTHEN THE HUMAN PROCESS (Singaporean Journal of Business Economics and Management, 2025)
The term ‘organizational development’ refers to a systematic organization-wide attempt implemented to achieve an increase in an organizations effectiveness and competitiveness. It, in a basic sense, attempts to implement a plan change to improve employee satisfaction and the productivity of an organization by strengthening the human processes of an organization (Neilsen, 1984: 2-3). Porras and Robertson (1992) define the term as: “A practical application of the science of organizations. Drawing from several disciplines for its models, strategies and techniques, OD focuses on the planned change of human systems and contributions to organization science through the knowledge gained from its study of complex change dynamics” (Porras and Robertson, 1992: 720). In this paper, we intend on critically assessing this definition of organizational development in relation to globalization’s impact on organizations, and organizational diversity. In order to do so, this paper will assess whether globalization creates a need for organizational development (defined according to Porras and Robertson), and whether organizational diversity is the response to this need. By doing so, this paper also intends on establishing a link between these two areas. In addition, due to the unevenness within the development of globalization, this paper will assess the areas of globalization and from a South African context.